Urgency Of Amendment To The Law On Human Rights Courts Regarding The Establishment Of AD HOC Human Rights Courts In Resolving Cases Of Gross Human Rights Violations In Indonesia - Bagas Valentinus Panjaitan; Christin Septina Basani (JURNAL HUKUM SEHASEN, 2024)
This research highlights the importance of changes in Indonesia's legal framework regarding the resolution of cases of gross human rights violations. By analyzing the urgency of changes to the Human Rights Court Law, this research links several relevant laws in this context. This research uses normative juridical research methods. The results show that the government has made efforts to deal with gross human rights violations through the establishment of the Non-Judicial Settlement Team for Past Gross Human Rights Violations. In addition, an ad hoc human rights court was established as a settlement mechanism for more complex and severe cases, but its establishment requires the approval of the House of Representatives based on certain events and a Presidential Decree. Law No. 26/2000 on Human Rights Courts became the legal basis for ad hoc human rights courts, replacing Law No. 1/1999 which had not been passed by the DPR. This regulation is regulated in the State Gazette of the Republic of Indonesia Year 2000 Number 208, which came into force on November 23, 2000. In addition to the role of the government, the community also has a role in resolving cases of gross human rights violations by reporting these events to relevant agencies such as the National Commission on Human Rights (Komnas HAM), especially if there are families or individuals who are victims.